Seven- to 11-year-olds’ developing ability to recognize natural facial expressions of basic emotions - Lang, Kathleen; Anthoney, Laura; Mitchell, Peter (SAGE, 2017)
Being able to recognize facial expressions of basic emotions is of great importance to social development. However, we still know surprisingly little about children’s developing ability to interpret emotions that are expressed dynamically, naturally and subtly, despite real-life expressions having such appearance in the vast majority of cases. The current research employs a new technique of capturing dynamic, subtly expressed natural emotional displays (happy, sad, angry, shocked and disgusted). Children aged 7, 9 and 11 years (and adults) were systematically able to discriminate each emotional display from alternatives in a 5-way choice. Children were most accurate in identifying the expression of happiness and were also relatively accurate in identifying the expression of sadness; they were far less accurate than adults in identifying shocked and disgusted. Children who performed well academically also tended to be the most accurate in recognizing expressions and this relationship maintained independently of chronological age. Generally, the findings testify to a well-developed ability to recognize very subtle naturally occurring expressions of emotions.